Dimensional control of interface coupling-induced ferromagnetism in CaRuO3/SrCuO2 superlattices - Li Zhe; Shi Wenxiao; Zhang Jine; Zheng Jie; Wang Mengqin; Zhu ZhaoZhao; Han Furong; Zhang Hui; Xie Liming; Yunzhong Chen; Fengxia Hu; Baogen Shen; et al. (NPG Asia Materials, 2024)
Abstract Due to the strong interactions from multiple degrees of freedom at the interfaces, electron-correlated oxide heterostructures have provided a promising platform for creating exotic quantum states. Understanding and controlling the coupling effects at the oxide interface are prerequisites for designing emergent interfacial phases with desired functionalities. Here, we report the dimensional control of the interface coupling-induced ferromagnetic (FM) phase in perovskite-CaRuO3/infinite-layered-SrCuO2 superlattices. Structural analysis reveals the occurrence of chain-type to planar-type structural transitions for the SrCuO2 layer as the layer thickness increases. The Hall and magnetoresistance measurements indicate the appearance of an interfacial FM state in the originally paramagnetic CaRuO3 layers when the CaRuO3 layer is in proximity to the chain-type SrCuO2 layers; this superlattice has the highest Curie temperature of ~75 K and perpendicular magnetic anisotropy. Along with the thickness-driven structural transition of the SrCuO2 layers, the interfacial FM order gradually deteriorates and finally disappears. As shown by the X-ray absorption results, the charge transfer at the CaRuO3/chain-SrCuO2 and CaRuO3/plane-SrCuO2 interfaces are different, resulting in dimensional control of the interfacial magnetic state. The results from our study can be used to facilitate a new method to manipulate interface coupling and create emergent interfacial phases in oxide heterostructures.